Identification of Blood Parasite on Sacrifical Cattle Slaughtered during Idul Adha 1438 H in Surabaya City and Sidoarjo Regency - Dhimar Maulud Dyahningrum; Mufasirin Mufasirin; Nenny Harijani; Poedji Hastutiek; Setiawan Koesdarto (Journal of Parasite Science (JoPS), 2019)
The aim of this research is to detect the presence of blood parasite that infects sacrificial cattle slaughtered during idul adha 1438 H in Surabaya City and Sidoarjo Regency. This research used 147 blood samples of sacrificial cattle and used two methods, those are thin blood smear stained with Giemsa 20% and Microhematocrit Centrifugation Technique. Based on the result of the examination using a microscope with 1000x magnification, there are positive samples infected with blood parasite, that consist of Babesia sp., and Anaplasma sp.